Sources of variability in hospital administrative data: Clinical coding of postoperative ileus. Issue 2 (May 2019) - Resslar, Mary A; Ivanitskaya, Lana V; Perez, Mario A; Zikos, Dimitrios
Background: Multiple studies have questioned the validity of clinical codes in hospital administrative data. We examined variability in reporting a postoperative ileus (POI). Objective: We aimed to analyse sources of coding variations to understand how clinical coding professionals arrive at POI coding decisions and to verify existing knowledge that current clinical coding practices lack standardised applications of regulatory guidelines. Method: Two medical records (cases 1 and 2) were provided to 15 clinical coders employed by a midsize nonprofit hospital in the northwest region of the United States. After coding these cases, the study participants completed a survey, reported on the application of guidelines, and participated in a focus group led by a health information management regulatory compliance expert. Results: Only 5 of the 15 clinical coders correctly indicated no POI complication in case 1 where the physician documentation did not establish a link between the POI as a complication of care and the surgery. In contrast, 13 of the 15 study participants correctly coded case 2, which included clear physician documentation and contained the clinical parameters for the coding of the POI as a complication of care. Clinical coder education, credentials, certifications, and experience did not relate to the coding performance. The clinical coders inconsistently prioritised coding rules and valued experience more than education. Conclusion and implications: The application of International Classification of Diseases, Ninth Revision, Clinical Modification; coding conventions; Centers for Medicare and Medicaid Services coding guidelines; and American Hospital Association coding clinic advice was subject to the clinical coders' interpretation; they perceived them as conflicting guidance. Their reliance on subjective experience in dealing with this conflicting guidance may limit the accuracy of reporting outcomes of clinical performance.